SEMANTIC TEACHING AND VOCABULARY LEARNING IN LANGUAGE LEARNING - Ganikhanova, Madina (Журнал иностранных языков и лингвистики, 2023)
In our article, is semantically devoted to the theory of teaching and vocabulary learning. The field method finds effective application in the study of the language of literary works. The need to expand the vocabulary of students is determined for various reasons. Life around, reading books, newspapers, and magazines, and listening to the radio and television programs enrich students ' knowledge, along with which often unfamiliar words come. Mastering knowledge at the same time involves memorizing new words.